Potensi Penerapan Model Koperasi Masjid Linked Program untuk Sustainability Keuangan Masjid - Binti Nur Asiyah; Lantip Susilowati; Moh. Taufiqur Rahman; Erina Wiji Lestari (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2023)
This study aims to determine the potential application of the linked program model as an effort to maximize the sustainability of mosque cooperatives. This research uses a qualitative approach, with the type of case study research. Sources of data were obtained through in-depth interviews with the manager of the mosque/mosque takmir cooperative, the Head of BIMAIS Kankemenag Tulungagung, LAZ, and the congregation of the mosque. Data analysis was carried out through the stages of data reduction, data presentation and conclusions. The results showed that the implementation of the mosque cooperative model has the socio-economic potential of the mosque in the form of revolving loans, buying and selling cheap basic necessities, fisheries, and zakat/qurban. The Linked Mosque Cooperative Program is implemented in collaboration with the Indonesian Mosque Council Program, the BAZNAS Program, the LAZ Program, the Indonesian Sharia Bank Program, and suppliers of fishery trading companies. In conclusion, the mosque model cooperative link program provides benefits for the financial sustainability of the mosque.